UPAYA MENINGKATKAN KETERAMPILAN SAINS ANAK KELOMPOK B MELALUI KEGIATAN PERCOBAAN SEDERHANA DI TK ISLAM AN-NUR PA’BANGNGIANG, KABUPATEN GOWA - Ayu Andira; Sukmawati; Arie Martuty (STKIP Subang, 2023)
The main problem in this study is how to improve the science skills of group B children by applying a simple experimental method at An-Nur Pa'bangngiang Islamic kindergarten, Gowa Regency. The type of research used is class action research consisting of planning, implementation, observation and reflection stages. The study subjects were and 16 children of group B2 at An-Nur Pa'bangngiang Islamic Kindergarten. The object of this study is to apply simple experimental activities to improve children's science skills. Data collection techniques used for observation and documentation. The data analysis used is a quantitative description. The results of this study show that there is an improvement in children's science skills through simple experimental activities in group B children at An-Nur Pa'bangngiang Islamic kindergarten. Research in cycle I and cycle II shows that children's science skills can be seen from the observational results of children's science skills in cycle I are 40.6% and the observational results of children's science skills in cycle II are 89.6% with Excellent Development criteria. Thus it can be concluded that by applying simple experimental activities can improve science skills in group B children at An-Nur Pa'bangngiang Islamic kindergarten.